Institutionalizing Premarital Screening: An Islamic Legal Politics Analysis through the Health Belief Model and Maqāṣid al-Sharīʿah - Irwansyah; Deniansyah Damanik (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2026)
Premarital screening remains voluntary in Indonesia, creating a policy gap in preventing hereditary diseases such as thalassemia despite increasing public health concerns. This study aims to analyze the politics of Islamic law regarding the institutionalization of premarital screening within Indonesia's national legal system by integrating the Health Belief Model (HBM) and the maqāṣid al-sharīʿah framework. This research adopts a qualitative socio-legal methodology that brings together doctrinal legal inquiry and empirical findings gathered through interviews with prospective marriage partners and key stakeholders. The findings demonstrate that public acceptance of premarital screening is strongly influenced by perceived susceptibility, perceived benefits, and health awareness as conceptualized in the Health Belief Model. From the perspective of Islamic legal politics, mandatory premarital screening represents a preventive legal policy that promotes the protection of life (ḥifẓ al-nafs) and lineage (ḥifẓ al-nasl), while also supporting the protection of intellect and property. The study further argues that institutionalizing premarital screening can be achieved through coordinated legal reforms involving the executive, legislative, and judicial branches. Although premarital screening is generally categorized within maqāṣid al-ḥājiyyāt, its strategic role in preventing genetic disorders justifies stronger legal intervention. This study contributes theoretically by integrating public health behavior with Islamic legal politics and offers practical recommendations for strengthening Indonesia's marriage and public health policies.